Pengaruh Profesionalisme, Kompetensi, Independensi, dan Moral Reasoning terhadap Kualitas Audit pada Kantor Akuntan Publik (KAP) di Kota Medan - Sherine Marcelline; Mahmuddin Syah Lubis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The auditor has a duty to assist or provide information about the objectives required by each shareholder, and other shareholders. The functions and duties of auditors such as tax audits, audits and financial statement analysis, the opinion of a qualified auditor can be useful for users. In the financial statements produce audited accountants can be accounted for by users as a basis for making a decision. The auditor must produce audited financial statements that can be trusted by users as a decision making decision. The population in this study includes all auditors who work in 33 Public Accounting Firms (KAP) in Medan City. The sample is 23 Public Accounting Firms (KAP) in Medan City with a sample of 62 accountants. The results of this study are professionalism that affects the quality of audits at the Public Accounting Firm (KAP) in Medan City. Competence affects the quality of audits at the Public Accounting Firm (KAP) in Medan City. Independence does not affect the quality of audits at the Public Accounting Firm (KAP) in Medan City. Moral reasoning does not affect the quality of audits at the Public Accounting Firm (KAP) in Medan City. Keyword : Professionalism, Competence, Independence, Moral Reasoning, Audit Quality